TINDAKAN PIDATO Pidato MOTIVASI USTADZ FAQIH SYARIF DALAM ACARA “SHAK TUHAN BESOK ADALAH JUMAT” DI SMART FM RADIO: SPEECH ACTS OF USTADZ FAQIH SYARIF’S MOTIVATIONAL SPEECH IN THE “THANKS GOD TOMORROW IS FRIDAY EVENT” ON SMART FM RADIO - Yudy Prasetyo; Abdul Syakur; Dina Merris (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study is to describe the locutionary forms of Ustadz Faqih Syarif’s motivation in the Thanks God Tomorrow is Friday event on Smart FM radio. Ustadz Faqih Syarif’s motivational illocutionary speech act in the thanks god tomorrow is Friday event on smart fm radio. The method used in this research is descriptive qualitative method. The method of data collection in this research is the method of listening. The source of this research data is a recording of the motivator event Ustadz Faqih Syarif in the Thanks god tomorrow is Friday event on smart Fm radio. Based on the presentation of the results of the research and discussion, it is concluded that the forms of locutionary speech acts in the Thanks God Tomorrow is Friday event are divided into two types, namely development techniques and indirect speech acts. development techniques are dominated by informative, descriptive speech acts, while narrative speech acts are declarative, interrogative and imperative.